2009
DOI: 10.1375/ajgc.19.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Factors Relevant to Secondary School Students in Australia, Singapore, the Philippines and Indonesia: Relative Differences and Congruencies

Abstract: Waldrip and Fisher (2000) proposed seven culturally relevant factors that are salient in the educational setting (gender equity, collaboration, competition, deference, modelling, teacher authority, congruence). In relation to these factors, the present study examined differences and congruencies in factor structure (i.e., differences of kind) and mean scores (i.e., differences of degree) among secondary school students in Australia, Singapore, the Philippines and Indonesia. The Cultural Learning Environment Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…For example, studies have demonstrated that age negatively predicted academic buoyancy (Martin, Colmar, Davey, & Marsh, 2010) and teacher-student relationships (Bracken & Crain, 1994), but it was a positive predictor of deep learning (Sadler-Smith, 1996) and flow experience (Sahoo & Sahu, 2009). Studies have also shown the role of language or ethnicity background in deep learning, resilience, the quality of teacherestudent relationship, and peer cooperation (den Brok & Levy, 2005;Leung, Ginns, & Kember, 2008;Liem, Martin, Nair, Bernardo, & Prasetya, 2009). Another factor to control is academic ability as, through its impact on self-efficacy and sense of control in learning, academic ability has been associated with deep learning, academic flow, academic buoyancy, the quality of student-teacher relationships, and peer cooperation (Bandura, 1997;Liem et al, 2008;Wentzel, 1997).…”
Section: Relevant Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies have demonstrated that age negatively predicted academic buoyancy (Martin, Colmar, Davey, & Marsh, 2010) and teacher-student relationships (Bracken & Crain, 1994), but it was a positive predictor of deep learning (Sadler-Smith, 1996) and flow experience (Sahoo & Sahu, 2009). Studies have also shown the role of language or ethnicity background in deep learning, resilience, the quality of teacherestudent relationship, and peer cooperation (den Brok & Levy, 2005;Leung, Ginns, & Kember, 2008;Liem, Martin, Nair, Bernardo, & Prasetya, 2009). Another factor to control is academic ability as, through its impact on self-efficacy and sense of control in learning, academic ability has been associated with deep learning, academic flow, academic buoyancy, the quality of student-teacher relationships, and peer cooperation (Bandura, 1997;Liem et al, 2008;Wentzel, 1997).…”
Section: Relevant Covariatesmentioning
confidence: 99%
“…Fourth, PBs-related research has predominantly been conducted in a culturally Western educational setting emphasizing individualism (Liem et al, 2009). There is a need for future studies to examine the effects of PB goals e that are characteristically personalized, self-set, and self-evaluated e among students in other cultural and educational contexts that operates on the basis of collectivist values and emphasizes the importance of togetherness, conformity, and deference to authority (e.g., teachers, parents).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The classroom context in particular reflects such collectivist tendencies, constituting, in effect, a social unit within the larger unit of society. Moreover, in the Indonesian context, TSIR is influenced by other pervasive cultural values, such as the idea of paternalism and respect for the authority of one's elders, which implicitly regulate the interaction between the young and the old (Liem, Martin, Nair, Bernardo, & Prasetya, ; Maulana et al ., ). As a consequence, the perceived distance between student and teacher is relatively high; also, the school system tends to be hierarchical and allows for little variation.…”
Section: Introductionmentioning
confidence: 99%
“…This is certainly what Liem, Martin, Nair, Bernardo, and Prasetya (2009) believe. They investigated how Southeast Asian students tend to conform to what the teacher says, as well as to what the majority of the class say.…”
Section: 'Being An Observer Is Problematic': Peer Feedback In Pt1 Classmentioning
confidence: 63%